ACTIVATION OF THE HYPOTHALAMIC– PITUITARY–ADRENAL AXIS INDUCES THE DIFFERENTIAL RELEASE OF PRO– INFLAMMATORY CYTOKINES IN BALB/C MICE - Gutierrez–Coronado, Oscar; Gutierrez, Paola T. Villalobos; Villasenor–Garcia, María Martha; Viveros–Paredes, Juan Manuel; Puebla–Perez, Ana Maria (European Scientific Journal, ESJ, 2015)
Physiological processes are associated with interactions between the nervous, endocrine and immune systems, which communicate through neurotransmitters, hormones and cytokines. The key to this communication is the hypothalamic–pituitary–adrenal (HPA) axis which can be activated by stress and pro–inflammatory cytokines. We have investigated the effects of acute and chronic stress on the release of pro–inflammatory cytokines through activation of the HPA axis. Accordingly, BALB/c mice were exposed to acute stress through the single application of bi–frontal electrical stimulation (ESa, 20V/10 mA/0.05s) and the effect produced by a single i.p. dose of Lipopolysacharide (LPS) (250 μg/100g). Chronic stress was (ESc) induced by applying the electrical stimulus to the animals in the same way for 7 consecutive days, as well as the effects of ascending LPS administration over 7 days (35–250 μg/100g i.p./day). Following stimulation, the levels of pro–inflammatory cytokines and corticosterone were quantified by ELISA. Unlike LPS that provoked an increase in TNF–α, IL–1β, IL–6, and corticosterone levels, acute electrical stress did not induce any change in the levels of pro–inflammatory cytokines or corticosterone. In contrast, chronic ESc stress produced an increase in the levels of TNF–α, while in the animals treated with LPS the IL–6 levels increased. These data suggest that the response of the HPA axis to stress depends on the duration, intensity and etiology of the stress agent, also suggest a suitable model for the evaluation of drugs with potential effect on inflammatory stress.